FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PENGETAHUAN IBU TERHADAP TANDA BAHAYA KEHAMILAN TRIMESTER III DI WILAYAH KERJA PUSKESMAS BINGIN TELUK KABUPATEN MUSI RAWAS UTARA - ruri maiseptya sari (CHMK MIDWIFERY SCIENTIFIC JOURNAL, 2021)
The cause of maternal death is late in recognizing danger signs during pregnancy and making a decision to refer, late in reaching a health facility, late in getting prompt and accurate help at a health facility. This study aims to study the factors related to maternal knowledge of the danger signs of pregnancy in the third trimester in the working area of ​​Bingin Teluk Public Health Center, Musi Rawas Utara Regency. This research is a quantitative study with a descriptive correlation design. The research design used cross sectional. The sample in this study were all third trimester pregnant women who were taken in total sampling of 42 people. Data collection techniques with primary data and secondary data. The data analysis technique used univariate and bivariate analysis with chi-square (????2) and contingency coefficient (C). Results: Of the 42 pregnant women, there were 20 mothers (47.6%) with less knowledge, 27 mothers (64.3%) aged 20-35 years, 17 mothers (40.5%) with basic education, 15 mothers ( 35.7%) with multiparous. There is a relationship between age, education and parity of pregnant women with knowledge of danger signs in the third trimester of pregnancy in the working area of ​​the Bingin Teluk Community Health Center, Musi Rawas Utara Regency. It is hoped that the Puskesmas will be able to provide more information related to the danger signs of pregnancy in the third trimester to pregnant women by providing counseling or giving leaflets for every pregnant woman doing ANC.